The use of vortex generators to reduce the aerodynamic drag of athletic apparel - Brownlie, L.; Aihara, Y.; Carbo Jr., J.; Harber, E.; Henry, R.; Ilcheva, I.; Ostafichuk, P. (Procedia Engineering, 2016)
In world-class athletic competitions the margin of victory is often exceedingly small and in a range that maybe influenced by aerodynamic drag (Fd). Vortex generators (VG) are small triangular or vane shaped protuberances that have been used successfully in automotive and aerospace applications to stir the boundary layer and delay flow separation over a wing or body surface. To determine if VG would reduce the Fd of a sprinter or marathon runner, a series of Fd measurements were conducted on circular cylinders, mannequin limb segments and full-scale mannequins in wind tunnels at the University of British Columbia and University of Washington. A large variety of VG shapes, sizes and patterns were developed using computer-aided design and rapid prototype printers. In total, the test program involved 1,540 discrete multi-velocity test runs requiring 56 days of wind tunnel time. The test program successfully identified specific arrangements of VG that, in combination with well-fitted garments, would reduce the Fd associated with running apparel by up to 6.8%, compared to the previous generation of advanced race apparel. Specific body maps based on race distance and gender were created to optimize the application of VG to different types of running apparel. Unlike previous apparel based drag reduction strategies that utilized multiple textured fabrics to reduce Fd, the VG based Fd reduction strategy provided three key advantages: (i) it became effective at a very low velocity and so can be used on apparel designed for either higher velocity (sprint) or lower velocity (marathon) running activities; (ii) it did not undergo a post-flow transition increase in Fd; and (iii) only a few rows of VG were normally required so that the weight and complexity of manufacturing the apparel were reduced. Mathematical modelling of sprint, middle distance and marathon performances at a world-class level suggest that aerodynamic apparel with VG could provide time savings of 0.013 seconds in 100 m, 0.50 seconds in 1500 m and 10.9 seconds in the marathon for male athletes wearing apparel with VG versus those wearing 2012 Olympic apparel without VG. The results of this study suggest that appropriate sizes and patterns of VG can provide a significant reduction in the Fd of running apparel.